2015
DOI: 10.1002/art.39055
|View full text |Cite
|
Sign up to set email alerts
|

Association of Severe Disc Degeneration With All‐Cause Mortality and Abdominal Aortic Calcification Assessed Prospectively in Older Men: Findings of a Single‐Center Prospective Study of Osteoporosis in Men

Abstract: Objective. To assess the association of disc degeneration with all-cause mortality and with the severity and rate of progression of abdominal aortic calcification (AAC) in older men.Methods. Men >50 years of age (n 5 766) underwent lateral spine radiography and blood collection and were monitored prospectively. We assessed the association of disc degeneration with all-cause mortality (at 10 years), AAC severity (at baseline), and AAC progression (at 7.5 years).Results. After adjustment for confounders, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…This study is strengthened by the large sample size of patients with the same pathology and 2-year follow-up data. The classification of AAC used in the study is widely accepted in multiple specialties 8,18,27,33 and has shown excellent (ICC > 0.9) interrater reliability in our analysis. Another benefit of this classification is that lateral lumbar radiographs are part of the presurgical workup and are thus readily available.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This study is strengthened by the large sample size of patients with the same pathology and 2-year follow-up data. The classification of AAC used in the study is widely accepted in multiple specialties 8,18,27,33 and has shown excellent (ICC > 0.9) interrater reliability in our analysis. Another benefit of this classification is that lateral lumbar radiographs are part of the presurgical workup and are thus readily available.…”
Section: Discussionmentioning
confidence: 70%
“…This study is strengthened by the large sample size of patients with the same pathology and 2-year follow-up data. The classification of AAC used in the study is widely accepted in multiple specialties 8,18,27,33 and has shown excellent (ICC . 0.9) interrater reliability in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that cardiovascular disease and related risk factors (abdominal aortic atherosclerosis in particular) are associated with disc degeneration and back pain [ 19 , 20 , 22 ], prompting speculation that treatment of cardiovascular risk factors/conditions might also help to prevent CBP or minimize its impact [ 22 , 42 44 ]. Results from our individual-level analyses of hypertension and CAD are consistent with earlier reports that these conditions are associated with future back pain or spine-related symptoms [ 18 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main medical conditions of interest for the current study measured at study baseline during the Men’s Health Study were arthritis, diabetes, hypertension, and CAD (which was considered a proxy for general atherosclerosis [ 19 22 ]). At the baseline assessment, participants reported whether they had ever previously been diagnosed with specific medical conditions, choosing from a list of common conditions, including “arthritis of any kind, or rheumatism”, “diabetes”, “hypertension or high blood pressure”, “coronary heart disease”, “asthma”, “chronic bronchitis”, “emphysema or chronic obstructive pulmonary disease”, “gastroesophageal reflux disease or reflux esophagitis”, “kidney disease”, or “liver disease”.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in aortic valve disease—where calcification was once thought to be the primary and near exclusive driver of valve dysfunction–men had more calcification than women at any given level of valvular stenosis (even after normalizing for body size or aortic root size) (1315), suggesting that valvular fibrosis may play a greater role in determining cusp movement in women compared to men. Similarly, the site of cardiovascular calcification seems to play an important role in predicting mortality in a sex-dependent manner, with thoracic aortic calcification being a strong predictor of mortality secondary to coronary events predominantly in women (16), whereas thoracic aortic and abdominal aortic calcification are strong predictors of all-cause mortality in men (17).…”
Section: The Clinical Justification For Exploring the Role Of Sex In mentioning
confidence: 99%